-2p+8=5-(7p+4)

Simple and best practice solution for -2p+8=5-(7p+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2p+8=5-(7p+4) equation:


Simplifying
-2p + 8 = 5 + -1(7p + 4)

Reorder the terms:
8 + -2p = 5 + -1(7p + 4)

Reorder the terms:
8 + -2p = 5 + -1(4 + 7p)
8 + -2p = 5 + (4 * -1 + 7p * -1)
8 + -2p = 5 + (-4 + -7p)

Combine like terms: 5 + -4 = 1
8 + -2p = 1 + -7p

Solving
8 + -2p = 1 + -7p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '7p' to each side of the equation.
8 + -2p + 7p = 1 + -7p + 7p

Combine like terms: -2p + 7p = 5p
8 + 5p = 1 + -7p + 7p

Combine like terms: -7p + 7p = 0
8 + 5p = 1 + 0
8 + 5p = 1

Add '-8' to each side of the equation.
8 + -8 + 5p = 1 + -8

Combine like terms: 8 + -8 = 0
0 + 5p = 1 + -8
5p = 1 + -8

Combine like terms: 1 + -8 = -7
5p = -7

Divide each side by '5'.
p = -1.4

Simplifying
p = -1.4

See similar equations:

| 3x+7=8x+13 | | 11x+=5x+37 | | 0.3(x+70)+1.5x=102 | | 3+p=9 | | -(3y+4)-(-2y-7)=-2 | | 144x^2-169y^2=0 | | 0.70x+.05(6-x)=.10(16) | | 8x^2+11xy+3y^2=0 | | x+12y+11x-13y-9= | | 8(x+5)=4(2x+3)+28 | | 4x-17=(3x-2)*4 | | 3x-3=7x+12 | | 4x=3y | | 3x-3=7x-12 | | 9x+5-4x-3+x=146 | | 2-6t-9-2t= | | -6-(2-3p)= | | -8n-9+7n= | | -[2z-(11z+1)]=1+(8z+6) | | x*0.1=20 | | -2z+11z+1=8z+6 | | 0.55x+.05(8-x)=.10(64) | | 20*x=0.1 | | -3+8x+4+(-10x)= | | -8y+(-2y)= | | 0.20(12)+0.05x=0.10(12+x) | | 7m+(-9m)= | | 74-2x=2x+22 | | 2x-5=4x+13 | | 8+2p-5=6p+8-3p | | -3x+12x= | | 7a+10a= |

Equations solver categories